Diabetes Care in Nigeria - Olufemi A. Fasanmade; Samuel Dagogo-Jack (Ubiquity Press, 2016)
Background: Diabetes is a noncommunicable disease that has attained great significance in the sub-Saharan region, with Nigeria being the most affected. Many persons with the condition suffer a reduced life expectancy and quality of life. Diabetes places an extra burden on the individuals and families affected, especially for the majority of patients unable to access quality health care. Objective: To describe the elements of diabetes management in Nigeria, areas for improvement, and proposed strategies to optimize care. Methods: A systematic literature search was performed on diabetes in Nigeria. Local and nonindexed literature, PubMed, and Google Scholar were used to source information on the subject. Findings: Diabetes-related morbidity and mortality continue to increase due to population expansion, urban migration, declining physical activity, and dietary factors. The organization of diabetes care is poorly coordinated, especially at the primary and secondary tiers of the public health care system, with consequent poor outcomes. Thus life expectancy (just about 50 years), which is low in the region, is further reduced by the double jeopardy of communicable (eg, tuberculosis, HIV/AIDS, and malaria) and noncommunicable diseases, such as diabetes and its closely related comorbidity, hypertension. Conclusions: The way forward is to improve maternal and child care, promote screening of at-risk populations, and develop strategies for primary prevention and early intervention to optimize glycemic control. Greater commitment to health care by the government and nongovernmental organizations and greater awareness by Nigerians should facilitate the desired improvements in disease prevention and glycemic control in those who are already affected.